Empowerment Of Bamboo Weaving Crafts Business In The “Aishwarya Asih” Business Group In Sulahan Village, Bangli Regency - Maharani, Ida Ayu Dinda Priyanka; Soraya, Dewi; P. Putra, I Gst. B Ngr (EQUATOR SINAR AKADEMIA, 2024)
Bangli Regency is rich in bamboo plants, namely plants belonging to the graminae family (grasses) and has a very flexible texture and is easy to create into various kinds of craft products. The business group that is a partner in the 2024 community service program is called the